Multidirectional in vitro and in cellulo studies as a tool for identification of multi-target-directed ligands aiming at symptoms and causes of Alzheimer's disease. (1st January 2020) - Szałaj, Natalia; Godyń, Justyna; Jończyk, Jakub; Pasieka, Anna; Panek, Dawid; Wichur, Tomasz; Więckowski, Krzysztof; Zaręba, Paula; Bajda, Marek; Pislar, Anja; Malawska, Barbara; Sabate, Raimon; et al.
Abstract: Effective therapy of Alzheimer's disease (AD) requires treatment with a combination of drugs that modulate various pathomechanisms contributing to the disease. In our research, we have focused on the development of multi-target-directed ligands – 5-HT6 receptor antagonists and cholinesterase inhibitors – with disease-modifying properties. We have performed extended in vitro (FRET assay) and in cellulo ( Escherichia coli model of protein aggregation) studies on their β-secretase, tau, and amyloid β aggregation inhibitory activity. Within these multifunctional ligands, we have identified compound 17 with inhibitory potency against tau and amyloid β aggregation in in cellulo assay of 59% and 56% at 10 µM, respectively, h BACE IC50 =4 µM, h 5TH6 K i =94 nM, h AChE IC50 =26 nM, and eq BuChE IC50 =5 nM. This study led to the development of multifunctional ligands with a broad range of biological activities crucial not only for the symptomatic but also for the disease-modifying treatment of AD.